(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Wakhidah AZ, Silalahi M, Yudiyanto. 2021. Ethnobotanical study of traditional steam bath bafufu in Lako Akediri Village, West Halmahera, Indonesia. Biodiversitas 23: 765-774. Indonesia’s high biological and cultural diversity has resulted in various plant uses for medicinal purposes, including for health steam bath or spa. Bafufu is a traditional steam bath performed by Lako Akediri villagers in West Halmahera, Indonesia which uses concoctions made from various plant species. It is usually used to maintain women’s bodies after postpartum and treat menstrual pain. This study was conducted to study the local knowledge of Lako Akediri villagers about bafufu spa concoction, including the diversity of plant and plant parts used to make the concoction and the community’s management of such plants, and the efficacy of the concoction. We conducted semi-structured interviews with 30 respondents, comprised of indigenous medical practitioners and local women. Additionally, we collected and identified the specimens of plants used in bafufu. We recorded 20 plant species used in bafufu with the most used parts of plants being leaves and fruits. The local community obtained plants from 3 sources, i.e., cultivation, semi-wild, or wild. As many as 7 species were cited more than 6 times with kananga [Cananga odorata (Lam.) Hook.f. & Thomson] is the most cited (10 citation). Those plants have been well studied regarding their phytochemical content in maintaining women’s reproduction health. Such most used plants have chemical compounds including liriodenine, punicalagins, curcumin, myristic acid, eugenol and citral a-citral b. The bafufu spa concoction has various benefits, such as maintaining the health of the reproductive organs reducing menstrual pain and body odor.